2021
DOI: 10.3390/life11010047
|View full text |Cite
|
Sign up to set email alerts
|

Chitin Synthases Are Critical for Reproduction, Molting, and Digestion in the Salmon Louse (Lepeophtheirus salmonis)

Abstract: Chitin synthase (CHS) is a large transmembrane enzyme that polymerizes Uridine diphosphate N-acetylglucosamine into chitin. The genomes of insects often encode two chitin synthases, CHS1 and CHS2. Their functional roles have been investigated in several insects: CHS1 is mainly responsible for synthesizing chitin in the cuticle and CHS2 in the midgut. Lepeophtheirus salmonis is an ectoparasitic copepod on salmonid fish, which causes significant economic losses in aquaculture. In the present study, the tissue-sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 69 publications
0
5
0
Order By: Relevance
“…These structures possibly separate from the parasite, potentially giving rise to new polymers shaping the subsequent copepodite stage. Chitin is present in the peritrophic matrix of these ectoparasites, covering the microvilli of their intestines [ 51 ], suggesting that effects on chitin could induce morphological changes in the intestine, influencing feeding behavior [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…These structures possibly separate from the parasite, potentially giving rise to new polymers shaping the subsequent copepodite stage. Chitin is present in the peritrophic matrix of these ectoparasites, covering the microvilli of their intestines [ 51 ], suggesting that effects on chitin could induce morphological changes in the intestine, influencing feeding behavior [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interfering with LmCHS2 transcription of Locusta migratoria reduced midgut chitin synthesis, resulting in high mortality of the insect ( Liu et al, 2012 ). The above studies have showed that changes in CHS gene expression led to the obstruction of insect development, deformity, molting difficulty, and even death, thereby affecting insect growth and development ( Roach et al, 2012 ; Tang et al, 2012 ; Contreras et al, 2016 ; Harðardóttir et al, 2021 ). We confirmed that ZK-PI-5 could directly reduce membrane-bound trehalase activity, and downregulate the expression level of SfTRE2 and SfCHS2 , lead to chitin metabolism disorder, affect chitin content and the growth and development of S. frugiperda , and lead to abnormal development and even death of S. frugiperda ( Figure 7B ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, dietary introduction of chitin synthesis inhibitors declines fecundity in A. aegypti [13]. In addition, RNAi of LsChS1 in pre-adult I results in deformation of ovaries and oocytes in adult Lepeophtheirus salmonis [40]. This result suggests the likelihood that CLS may also be present in eggshells and deficiency of CLS causes misshapen eggs in other arthropods.…”
Section: E Signal Triggers the Production Of A Clsmentioning
confidence: 99%